Non-English University Students Motivation in Learning English Online - Safira Naila Farihah; Atik Umamah (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
This research was conducted to investigate non-English university students’ motivation in learning English online based on their English achievement. This qualitative study involves 31 Indonesian language students from the fourth semester of a private university in Malang. The questionnaire data used by students were grouped into two items; Intrinsik motivation and Extrinsic motivation adopted from Subakhtiasih and Putri, (2020). Based on the total participant average scores, two students were involved in semi-structured interviews. These students were recruited based on two criteria: 1) Student is a high achiever in class. 2) Student is a low achiever in class. The students were asked what is the motivation to learn English and how do they manage their time and achieve their learning goals to stay motivated during online learning English. The data of the questionnaire and the interview was analyzed using content analysis. To triangulate the data, investigator triangulation was performed by involving two data analysts. The result of this research is that student motivation is at a moderate level. Students combine intrinsic motivation and extrinsic motivation to motivate them to learn English online. Furthermore, students have an effective way (e.g. time management and target goals) to stay motivated while studying English online.